Studies on polycyclic aromatic hydrocarbons in two sediment cores from the huaxi reservoir, china: Assessment of levels, sources, and ecological risk. Issue 1 (2nd January 2018) - Wang, Long; Han, Mengshu; Li, Qiuhua; Jiang, Fan
ABSTRACT: This study investigated the levels, sources and ecological risks of 16 polycyclic aromatic hydrocarbons (PAHs) in two sediment cores that were collected along the Huaxi Reservoir. The spatial distributions and residue levels of the 16 priority PAHs in the sediments from the Huaxi Reservoir were analyzed for their potential ecological risk, source apportionment and contribution to the total PAH residue. The concentration level of the total PAHs (TPAHs) was in the range 1805 ng·g −1 to 20023 ng·g −1 based on dry weight, and the content of PAHs in the Huaxi Reservoir exhibited a gradual upward trend. The PAH congener ratios fluoranthene/(fluoranthene + pyrene) and indeno[1, 2, 3-cd]pyrene/(indeno[1, 2, 3-cd]pyrene + benzo[g, h, i]perylene) were used to identify the source. The main source of the low molecular weight PAHs was wood and coal combustion, whereas the high molecular weight PAHs were primarily from petroleum combustion sources. The results of an ecological risk assessment demonstrated that ACE poses a potential ecological risk, while FLU, NAP, ANT, BaP, DBA, PHEN and PYR can have serious ecological risks.